4th International Conference on Imaging for Crime Detection and Prevention 2011 (ICDP 2011) 2011
DOI: 10.1049/ic.2011.0101
|View full text |Cite
|
Sign up to set email alerts
|

Self-dependent 3D face rotational alignment using the nose region

Abstract: One of the challenging issues for 3D face recognition is face alignment. Many alignment algorithms are computationally expensive, making them unsuitable for real-time biometrics, or not robust enough to detect large variations in pose. In this work, a novel algorithm for 3D face rotational alignment is proposed, that uses the nose region. After preprocessing and nose region identification, alignment is performed by apply ing two energy functions to the nose footprint, identified as the largest filled region in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…To do this, the principal curvature and shape index (SI) are computed and the SI is scaled so that its maximum and minimum values are exactly +1 and -1, receptively. The face's convex regions are found by thresholding the SI to produce a binary image, using -1 < SI < − 5 8 [3,1,5,7]. The largest connected component is detected and its boundary is smoothed by dilating with a disk structuring element.…”
Section: Denoising Tip Detection and Face Croppingmentioning
confidence: 99%
See 3 more Smart Citations
“…To do this, the principal curvature and shape index (SI) are computed and the SI is scaled so that its maximum and minimum values are exactly +1 and -1, receptively. The face's convex regions are found by thresholding the SI to produce a binary image, using -1 < SI < − 5 8 [3,1,5,7]. The largest connected component is detected and its boundary is smoothed by dilating with a disk structuring element.…”
Section: Denoising Tip Detection and Face Croppingmentioning
confidence: 99%
“…1(d). This approach to nose region cropping results in fewer redundant regions than the approach of [5] and is much faster than that of [4] which uses level set based contours.…”
Section: Alignment and Nose Croppingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the nasal region, which is more consistent over universal expressions and also invariant to the majority of occlusions caused by hair, hands and scarves [1][2][3][4][5], is widely used in many face recognition algorithms. Mian et al [3] found the forehead is also relatively invariant under basic expressions.…”
Section: Introductionmentioning
confidence: 99%